Smart questions : - Nadler, Gerald (A Wiley, 2004)
Smart Questions offers an entirely new framework for creating solutions. Drawn from the authors' many years of research and field experience, the Smart Questions Approach reveals how the leading creators of solutions in almost every profession and walk of life—including business, government, education, and even in families—think and approach their assignments. The author’s holistic thinking approach shows how to use three “foundation” questions—focusing on uniqueness, purposeful information, and systems—which must be explored for every problem. These three questions, an essential starting point for exploring problems, in turn lead to other key questions that will ultimately create effective solutions.